Chapter Sugli italianismi di trafila indiretta in russo - Gherbezza, Ettore (Biblioteca di Studi Slavistici, 2018)
The aim of the present study is to investigate some manifestations of language contact between Italian and Russian, and in particular lexical Italianisms acquired indirectly by passing from other European languages and then into Russian. Special attention is paid to methodological issues, in order to locate the study of lexical contact phenomena between Italian and Russian within the broader field of the study of Italianisms in other European languages.